2022
DOI: 10.1148/radiol.212873
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Multiparametric MRI–based Radiomics Models for Preoperative Risk Stratification of Endometrial Cancer

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 32 publications
5
26
1
Order By: Relevance
“…Endometrial cancer is the sixth most common malignant disorder worldwide with an estimated 382,000 new cases diagnosed annually [ 1 ]. Magnetic resonance imaging (MRI) has been extensively applied in endometrial cancer staging [ 2 , 3 , 4 , 5 ] and is usually the imaging modality of choice for assessment of deep myometrial invasion (DMI) [ 6 , 7 , 8 , 9 ]. Studies have shown that using MRI alone, endometrial cancer DMI prediction [ 10 ] accuracies were estimated to be 74% [ 11 ], 76% [ 12 ], and 89% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endometrial cancer is the sixth most common malignant disorder worldwide with an estimated 382,000 new cases diagnosed annually [ 1 ]. Magnetic resonance imaging (MRI) has been extensively applied in endometrial cancer staging [ 2 , 3 , 4 , 5 ] and is usually the imaging modality of choice for assessment of deep myometrial invasion (DMI) [ 6 , 7 , 8 , 9 ]. Studies have shown that using MRI alone, endometrial cancer DMI prediction [ 10 ] accuracies were estimated to be 74% [ 11 ], 76% [ 12 ], and 89% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these accuracies are subjective as it is dependent on the radiologist’s ability to detect subtle imaging textures on MR images. To overcome these limitations, radiomics [ 14 , 15 ], which extracts quantitative image features from medical imaging, has been proposed to predict DMI [ 8 , 9 , 16 ]. Nevertheless, relatively few studies to date have focused on identifying clinical prognostic factors other than stage, using radiomic features from MRI [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For proper measurement of ADC values, the ROI should be placed to avoid any areas of necrosis and cystic components of the lesion to avoid false elevation of values [ 44 ]. Three dimensional radiomics using DWI can help identification of endometrial cancer patients with high-risk histopathological factors such as advanced stage and deep myometrial invasion [ 45 ]. However, the study by Bereby-Kahane et al, reported limited value of radiomics analysis based on T2-weighted and DWI MRI [ 46 ].…”
Section: Clinical Applications In Gynecological Malignanciesmentioning
confidence: 99%
“…The use of radiomics, a quantitative image analysis method that is used to extract a large number of features from medical image data, has been proposed to increase the diagnostic and prognostic imaging yield in a variety of conditions [5][6][7]. Recently, studies have highlighted the potential of radiomics for the identification of fetuses with abnormal lung development and texture-based neonatal respiratory distress prediction [8][9][10].…”
Section: Introductionmentioning
confidence: 99%